Three-dimensional structure modeling of a protease from lactic acid bacteria Leuconostoc mesenteroides K7 using automated protein homology analysis - Habibi HIdayat; Winarto Haryadi; TRI JOKO RAHARJO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hidayat H, Haryadi W, Raharjo TJ. 2020. Three-dimensional structure modeling of a protease from lactic acid bacteria Leuconostoc mesenteroides K7 using automated protein homology analysis. Biodiversitas 21: 3156-3162. This study aimed to characterize the protease encoding gene of Leuconostoc mesenteroides K7 isolated from Kelengkeng (Dimocarpus longan) fruit as well as to predict the structure of the protein using in silico approach. Gene characterization was performed using PCR employs primers designed based on protease gene of other Leuconostoc species, followed by cloning and sequencing of the PCR product. Protein structural modeling was targeted to the deduced amino acid sequence of the gene employ multiple sequence alignment and SWISS-Model online software.  As a result, the sequence of the PCR product contains an open reading frame with a size of 1,140 bp, which can be translated into 379 amino acids. The amino acid sequence shares 98.60% identity with protease from Leuconostoc suionicum (AP017935.1). Three conserved sequences of QTDA, INPGNSGGPL, and FAIP are known as the signature from the Serine endoprotease DegS family are detected.  The three-dimensional modeling structure application shows that the protein share similarity of 37.62% to Protease Do-like I chloroplastic that belong to serine protease.